Endovascular retrieval of an elongated Supera stent - Naoya Otaka, MD, PhD; Toshiki Kawamiya, MD, PhD; Jun Ohno, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques, 2022)
Stenting is used to achieve artery patency, and the Supera stent, a self-expanding interwoven nitinol stent, has produced good clinical outcomes. A 70-year-old woman with peripheral artery disease had experienced intermittent claudication (Fontaine stage IIb). Endovascular treatment was performed for a chronic total occlusion TransAtlantic InterSociety Consensus class II type B lesion. A Supera stent (Abbott Vascular, Santa Clara, CA) was used. However, it had become severely elongated to the proximal end in the superficial femoral artery and was removed using a balloon inserted from the side and trapped to the guide sheath with the distal end of the stent outside the sheath. After this bailout, an alternate stent could be placed through an antegrade approach to the contralateral common femoral artery.